An Analysis of Social Action in Ketadu Mara Traditional Music Activities in Sabu Raijua Regency through Max Webers Perspective - Makdalena Yuniati Hege Udju; Udi Utomo (Riwayat: Educational Journal of History and Humanities, 2025)
The traditional music art of Ketadu Mara in Sabu Regency possesses a distinctive sound and song lyrics derived from everyday life. This study aims to examine the musical activities of Ketadu Mara through Max Webers social action theory. As a cultural heritage of the Sabu community, Ketadu Mara holds a significant role as a social practice rich in symbolic meanings, cultural values, and social functions. This research employs a descriptive qualitative method with phenomenological and sociological approaches. Data were collected through participatory observation and in-depth interviews with local artists and cultural community members in Ledeana Village, which serves as a center for preserving Ketadu Mara. The findings reveal that Ketadu Maras musical activities reflect two dominant types of social action according to Weber: traditional action, which is inherited across generations without formal instruction, and value-rational action, driven by beliefs in cultural values, ancestral reverence, and spiritual devotion. Beyond serving as entertainment and a means of cultural preservation, Ketadu Mara also functions as a medium for symbolic communication, identity formation, and education for younger generations. Thus, Ketadu Mara plays a crucial role in strengthening social solidarity and sustaining local cultural existence amidst the tides of change.